The strategy to leverage financing disbursement: Bank owned by regional Banks Indonesia - Jusni, Andi Aswan,; Taufiq Possumah, Bayu (Opción, 2019)
The study was intended to investigate three predicted variables that is believed as an effective strategy to leverage financing disbursement. Those variables are bank size, risk repayment, and efficient. Three regression tests conducted were common effect, fixed effect and random effect. Of three regressions analysis conducted, three statistical results indicate random effect was the best regression coefficient for data as given by Chow and random effect test. To statistical result, as predicted, risk repayment and efficiency contributed to have a negative sign to leverage financing disbursement.